2021
DOI: 10.3390/pathogens10020145
|View full text |Cite
|
Sign up to set email alerts
|

Leptospiral Infection, Pathogenesis and Its Diagnosis—A Review

Abstract: Leptospirosis is a perplexing conundrum for many. In the existing literature, the pathophysiological mechanisms pertaining to leptospirosis is still not understood in full. Considered as a neglected tropical zoonotic disease, leptospirosis is culminating as a serious problem worldwide, seemingly existing as co-infections with various other unrelated diseases, including dengue and malaria. Misdiagnosis is also common as non-specific symptoms are documented extensively in the literature. This can easily lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
84
0
12

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 222 publications
(199 reference statements)
0
84
0
12
Order By: Relevance
“…Alternatively, the development of efficient vaccines and drugs is also necessary. Rational development of diagnostic tools and vaccines requires a clear understanding of the molecules used as candidates or targets for this purpose [ 2 ]. Secretory proteins are a group of molecules from which better molecules for an anti-leptospiral strategy can be obtained because of their biological significance concerning pathogenesis and host-pathogen interactions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the development of efficient vaccines and drugs is also necessary. Rational development of diagnostic tools and vaccines requires a clear understanding of the molecules used as candidates or targets for this purpose [ 2 ]. Secretory proteins are a group of molecules from which better molecules for an anti-leptospiral strategy can be obtained because of their biological significance concerning pathogenesis and host-pathogen interactions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leptospirosis is one of the most important zoonotic diseases caused by pathogenic species of the spirochete bacteria Leptospira [ 16 , 17 ]. This disease is considered a neglected and re-emerging disease of global public health significance, which causes high mortality and morbidity in both humans and animals [ 18 , 19 ]. Nowadays, outbreaks of leptospirosis occur in tropical countries, particularly India, Malaysia, and Brazil [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leptospirosis cases were found to increase due to heavy rainfall, flooding, and poor sanitation, which frequently occur in urban slum areas [ 20 , 21 ]. Previous studies demonstrated the incidence of leptospirosis increasing and being widespread in Italy, Pakistan, Japan, Nicaragua, the Philippines, and Sri Lanka [ 17 , 18 ]. At least 1 million leptospirosis cases have been reported worldwide, with nearly 60,000 deaths per year [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations